2014
DOI: 10.18632/oncotarget.2546
|View full text |Cite
|
Sign up to set email alerts
|

STAT3 inhibition suppresses proliferation of retinoblastoma through down-regulation of positive feedback loop of STAT3/miR-17-92 clusters

Abstract: Retinoblastoma, the most common intraocular malignant tumor in children, is characterized by the loss of both functional alleles of RB1 gene, which however alone cannot maintain malignant characteristics of retinoblastoma cells. Nevertheless, the investigation of other molecular aberrations such as matrix metalloproteinases (MMPs) and miRNAs is still lacking. In this study, we demonstrate that STAT3 is activated in retinoblastoma cells, Ki67-positive areas of in vivo orthotopic tumors in BALB/c nude mice, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
37
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 33 publications
1
37
0
Order By: Relevance
“…It was found that downregulation of STAT3 using RNA interference targeting STAT3, and small molecule inhibitors suppressed tumor cell proliferation and invasion, induced apoptosis in vitro, and delayed tumor growth in animal models of various types of cancer (32)(33)(34). Recently, a study showed that STAT3 expression was increased in RB tissues from human patients compared to normal retinal tissues, and that inhibition of STAT3 in RB cells with targeted siRNAs resulted in impaired proliferation and downregulation of target genes in vitro, and suppressed formation of orthotopic tumors in vivo (35), suggesting STAT3 is an oncogene in RB. Although STAT3 has been reported to be a target of miR-124 in several types of cancers, such as esophageal cancer (18), glioblastoma (19), hepatocellular carcinoma (20) and non-small cell lung cancer (21), however, the interaction between miR-124 and STAT3 has not been experimentally validated in RB.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that downregulation of STAT3 using RNA interference targeting STAT3, and small molecule inhibitors suppressed tumor cell proliferation and invasion, induced apoptosis in vitro, and delayed tumor growth in animal models of various types of cancer (32)(33)(34). Recently, a study showed that STAT3 expression was increased in RB tissues from human patients compared to normal retinal tissues, and that inhibition of STAT3 in RB cells with targeted siRNAs resulted in impaired proliferation and downregulation of target genes in vitro, and suppressed formation of orthotopic tumors in vivo (35), suggesting STAT3 is an oncogene in RB. Although STAT3 has been reported to be a target of miR-124 in several types of cancers, such as esophageal cancer (18), glioblastoma (19), hepatocellular carcinoma (20) and non-small cell lung cancer (21), however, the interaction between miR-124 and STAT3 has not been experimentally validated in RB.…”
Section: Discussionmentioning
confidence: 99%
“…Khurram et al [9] reported that activation of the XCL1-XCR1 pathway could promote the expression of MMP2 and MMP9 in oral cancer cells. Furthermore, MMP2 and MMP9 were also considered as the downstream of JAK2/STAT3 pathway [15,16]. However, no correlation of XCL1/XCR1 and MMPs in lung cancer has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…4E). Meanwhile, activation of XCR1 was reported to increase the expression of matrix metalloproteinase 2 (MMP2) and MMP9 in oral cancer cells [9], which were also regulated by STAT3 [15,16]. We detected the role of XCL1/XCR1 in regulating MMP2 and MMP9 in lung cancer by qRT-PCR, and found that XCL1 up-regulated the mRNA level of MMP2 and MMP9 in a dose-dependent manner.…”
Section: Xcl1/xcr1 Activates Jak2/stat3 Pathwaymentioning
confidence: 94%
“…Several reports showed that these miRNAs form important network motifs with MYC in Bcell lymphoma (Mihailovich et al, 2015), with E2F/MYC (Y. Li, Li, Zhang, & Chen, 2011) and with STAT3 in retinoblastoma (Jo et al, 2014). This biology-inspired in silico experiments enabled us to propose a minimal model of gene dosage compensation for MYC and STAT3 out of experimentally-validated interactions.…”
Section: Discussionmentioning
confidence: 90%